Problem koekwacji ofiary wieczystej w czasie lutowych posiedzeń Sejmu w 1790 r. - Wróblewski, Bartosz (Acta Universitatis Lodziensis. Folia Historica, 2001)
Seym in periods 1788-1792 made a wide reform program for example they changed the financial system. On 26 March 1789 it was imposed a new tax which took 10% of profits from every nobility fortune. It was the first, in the history of Polish and Lithuanian Union, the permament taxation from profits which was made on nobility land. But this taxation was unsatisfactory. Unfortunately the owners of the land had to count their own profits. New taxes caused many problems in the south-east territory of Poland. The land owners complained that they had to pay too many taxes, more than in any other parts of Poland for example Wielkopolska. It caused in February especially on 19 and 22 of February a debate in Seym about the instituted commission of koekwacia. This discussion is a principle subject of my article. This commission should have raised the tax up to real 10% from profits and suppress disproportion. The basic work of this commission was the idea of Fryderyk Moszyński who was the member of the Seym. He made a plan that the profits from possession could be estimated on the basic price of lands in provinces during the periods 1778-1788. This project caused strong opposition among the delegats from the rich province of Wielkopolska (where land prices were high) but it was supported by the delegats from the south-eastern territory, where the prices of possession were low. I try to show this discussion and special economical and historical questions, which were important in the discussion. I will show the way to achieve the compromise during the debates. In finish koekwacia commission agreed that the taxation in Wielkopolska was too low. The commission raised the taxation. Unfortunately the full achievement of the commission work was blocked by the Russian invasion in 1792.